Bodily distress syndrome: reuniting what other specialities have divided - Nunes, José M. Mendes (2017)
The author defends the concept of the bodily distress syndrome (BDS) as a unifying entity of somatic syndromes and somatoform symptoms. These patients have physiological, cognitive, and behavioural characteristics that require a comprehensive approach. We require the integration of a number of pseudo-diagnoses that are side effects of medical specialization. Patients most in need of a holistic view are paradoxically disintegrated by the approach of many medical specialties. They simply add diagnostic labels that reduce the patient’s perception of health. The concept of BDS accepts the complexity of these symptoms. It rejects the mind-body duality and the negative definition of the condition as the absence of a medical explanation. Because this approach depends on the doctor-patient relationship and continuity of care, the family physician is primarily responsible for addressing the needs of these patients, with rational use of referral to other specialties.